SUBSTITUSI TEPUNG LABU KUNING (Cucurbita moschata Durch) DAN KORO PEDANG (Canavalia ensiformis L.) TERHADAP TERIGU PADA PEMBUATAN CAKE - Pratiwi Loelinda; Ahmad Nafi'; Wiwik Siti Windrati (JURNAL AGROTEKNOLOGI, 2017)
Cake is one of the products bakeries. The main ingredient on the production of cake is wheat. Until now, Indonesia still imports wheat from other countries. Thus, to reduce wheat consumption can use food diversification such as pumpkin and jack bean. Jack bean (Canavalia ensiformis L.) has protein and carbohydrate content 24% and 25% respectively. Pumpkin (Cucurbita moschata Durch) is one of the agricultural commodities has protein and carbohydrate content 1,1,% and 6,6% respectively. The purpose of this research are to know the effect of pumpkin and jack bean flour on the physic and organoleptic characteristic of cake, to know the best formulation of pumpkin and jack bean flour. The best treatment cake is P5 (50% flour: 10% yellow pumpkin flour: 40% jack bean flour). Cake was 0hue at 92,20 which shows yellowish white color, chroma value at 22,26, expandability is 230,38%, staleness of day 0 at 42,72%, Δ change on day 0 to1 by 1.96%, Δ change on day 1 to 2 by 2.73%, effectivity test at 0,54% , Water content 38,26%, ash content 0,96%, fat content 4,01%, protein content 28,28%, and carbohydrate content 31,47%. Keywords: cake, pumpkin, jack bean